Perovskite structure mixed ion-electron conductor material and application thereof in lithium battery

By introducing variable valence transition metal elements into the hybrid ion-electronic conductor materials of perovskite structure and embedded lithium reaction, the problems of interface impedance and lithium dendrites of lithium batteries are solved, and the high-rate performance and long cycle of lithium batteries are achieved life.

CN119446623APending Publication Date: 2025-02-14BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411401274.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing inorganic solid electrolytes have a large interface impedance at the lithium metal negative electrode, resulting in lithium dendrites generation and interface instability, affecting the high energy density and cycling stability of the battery.

Method used

By introducing variable valence transition metal elements into the hybrid ion-electron conductor material of perovskite structure, and improving the electronic conductivity of the material through lithium embedded reaction, forming mixed ion-electron conductor monomers to improve the interface stability of lithium batteries. and electrochemical properties.

Benefits of technology

实现了锂电池界面稳定性和电化学性能的提升,包括提高了倍率性能和循环寿命,降低了锂枝晶生成,增强了电池的安全性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention discloses a perovskite structure mixed ion-electron conductor material and application thereof in a lithium battery, and belongs to the technical field of lithium batteries. The general formula of the material is Li [alpha] Sr [beta] X [x] Ta1-y-zYyZzO3, wherein 0.12 < = alpha < = 0.56, 0.3 < = beta < = 0.44, 0.56 < = alpha + beta + x < = 1, 0.11 < = z < = 0.23, and 0.11 < = y + z < = 0.50. Enough free electrons are obtained in a mode of embedding and reducing the variable valence element Z by the metal lithium, and the conductivity property of the electrons is obtained. The mixed conductor has high ionic conductivity, high electronic conductivity can be obtained in an in-situ or ex-situ mode through lithium intercalation, and the interface stability and rate capability are improved. The method can be applied to an electrode interface, such as a filling electrode active particle gap and a negative electrode / electrolyte interface layer in a battery, and can be applied to devices such as a lithium ion battery, a metal lithium battery and an all-solid-state lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to inorganic solid electrolytes and all-solid-state batteries, and in particular to applications of perovskite-type mixed ion-electron conductor (mixed conductor) materials and composite mixed conductor materials containing the materials in electrodes / electrolytes. Background Art

[0002] Among common energy storage battery devices, lithium-ion secondary batteries have good comprehensive performance. With the advantages of high energy density and long cycle life, they are widely used in large-scale energy storage, electric vehicles, electronic products and other industries. Traditional lithium-ion batteries mostly use flammable organic electrolytes, which leads to safety hazards. Compared with traditional organic electrolytes, inorganic solid electrolytes are non-flammable, safe, have a wide electrochemical window, and have the possibility of matching high energy density metal lithium negative electrodes. They have received widespread attention in the research and development of the next generation of high energy density lithium-ion batteries (W.Zhao, J.Yi, P.He, H.Zhou, Electrochemical Energy Reviews 2019, 2, 574-605).

[0003] The common problem of most inorganic solid electrolytes is that they will generate large interfacial impedance when in solid-solid contact with lithium metal negative electrodes, and the uneven electric field at the interface and the presence of grain boundaries directly lead to the generation of lithium dendrites at the interface and growth along the grain boundaries (Y.Liu, X.Xu, X.Jiao, O.Kapitanova, Z.Song, S.Xiong, Advanced Materials 2023, 35, 2301152). The growth of dendrites inside the electrolyte is mainly driven by overpotential and continuous electron injection. When the overpotential exceeds the lithium nucleation potential, lithium will nucleate at the electrode interface and internal defects of the electrolyte, and the growth of lithium dendrites will be uncontrollable (A.Pei, GYZheng, FFShi, YZLi, Y.Cui, Nano Lett 2017, 17, 1132). Therefore, the high energy density negative electrode interface kinetics and long-term cycle stability are major challenges. To solve this problem, an interface modification layer can be introduced between lithium metal and the solid electrolyte. The interface modification layer can increase the electrode / electrolyte wettability, reduce the interface resistance, and improve the interface stability. Interface modification materials mainly include electronic conductors, ion conductors, and mixed electronic-ion conductors (X.-B. Cheng, C. Yan, X.-Q. Zhang, H. Liu, Q. Zhang, ACS Energy Letters 2018, 3, 1564; C. Wang, L. Zhang, H. Xie, G. Pastel, J. Dai, Y. Gong, B. Liu, ED Wachsman, L. Hu, Nano Energy 2018, 50, 393). Mixed ion-electronic conductive materials have the advantages of the previous two. They can not only effectively promote the migration kinetics of lithium ions, but also homogenize the electric field distribution and induce uniform lithium deposition (J. Gao, J. Zhu, X. Li, J. Li, X. Guo, H. Li, W. Zhou, Advanced Functional Materials 2021, 31, 2001918).Generally, there are two ways to form a mixed conductor interface modification layer. One is to introduce a class of compounds to react with the metallic lithium negative electrode to form a nanoporous composite mixed ion / electron conductor (H. Huo, Y. Chen, R. Li, N. Zhao, J. Luo, J. Silva, R. Mücke, P. Kaghazchi, X. Guo, X. Sun, Energy Environ Sci 2020, 13, 127); the other is to trace-dope the fast ion conductor with variable-valence elements, and reduce the valence state of the doped elements to a low-valence state by in-situ lithium insertion, which can improve its electronic conductivity and make the material have mixed ion-electron conductivity (J. Zhu, X. Li, C. Wu, J. Gao, H. Xu, Y. Li, X. Guo, H. Li, W. Zhou, Angew Chem Int Ed 2021, 60, 3781-3790). Compared with the composite phase mixed conductors formed by conversion reactions, the mixed conductive monomers formed by doping and lithium insertion can avoid phase separation and have a relatively more stable structure during the charging and discharging process. Lithium ions and electrons are conducted in the same phase, avoiding the interface impedance problem caused by different lithium ion and electron conduction pathways in the composite phase, which can improve the battery's rate performance and cycle life.

[0004] For perovskite solid electrolytes, such as Li 0.33 La 0.57 TiO3 (MJ Wang, JB Wolfenstine, J. Sakamoto, Advanced Functional Materials 2020, 30, 1909140), in which the transition metal element Ti is not stable to the metal lithium negative electrode. During the battery cycle, Ti 4+ May passively revert to Ti 2+ Or Ti 0 , because the content of Ti in the electrolyte is too high, it greatly increases the electronic conductivity and increases the risk of battery short circuit. 4+ The reduction of Ti improves the electronic conductivity, proving that it can be used as a conductive additive for composite anodes. Unlike passive reduction of Ti, by limiting the Ti content, that is, actively doping a trace amount of Ti at the negative electrode / electrolyte interface, the amount of Li insertion / extraction can be quantitatively controlled, and the free electron concentration in the material and the stability of the material can be balanced.

[0005] For Sr-based perovskite electrolytes, Bing Huang, CH Chen, Ryoji Inada and others carried out element doping modification based on the structure. 3 / 8 Sr 7 / 16 Hf 1 / 4 Ta 3 / 4O3(B.Huang,B.Xu,Y.Li,W.Zhou,Y.You,S.Zhong,C.Wang,J.Goodenough,ACS Appl Mater Interfaces 2016,8,14552-14557), Li 3 / 8 Sr 7 / 16 Ta 3 / 4 Zr 1 / 4 O3 (CH Chen, S. Xie, E. Sperling, A Yang, G. Henriksen, K. Amine, Solid State Ionics 2004, 167, 263-272; R. Inada, K. Kimura, K. Kusakabe, T. Tojo, Y. Sakurai Solid State Ionics 2014, 261, 95-99), the main purpose of this type of doping is to explore the relationship between the defective local structure and ionic conductivity after doping, so as to improve the lithium ion conductivity of the electrolyte and the stability of the material when in contact with the lithium negative electrode. However, since this type of structure does not contain variable valence metal elements, although lithium vacancies exist naturally and Li is embedded to a certain extent, the amount is uncontrollable, and it is not possible to generate uniform and stable electronic conductive materials.

[0006] Hiroyuki Watanabe et al. studied the Sr-based perovskite solid electrolyte Li 2x Sr l-2x M 0.5-x Ta 0.5+ x O3 (H. Watanabe, J. Kuwano, Journal of Power Sources 1997 68, 421-426). Where M = Cr, Fe, Co, Al, Ga, In, Y, and all are positive trivalent. The main purpose of this article is to screen out elements that can significantly improve ionic conductivity after doping. Similarly, Yoshiyuki Inaguma et al. studied and designed the perovskite electrolyte Li x Sr 1-x Ta x Ti 1-x O3 (0.3 ≤ x ≤ 0.5) (Y. Inaguma, Y. Matsui, Y. Shan, M. Itoh, T. Nakamura, Solid State Ionics 1995, 79, 91-97), the main purpose of this article is to adjust the content of LiTaO3 and SrTiO3 to obtain materials with high ionic conductivity; and the designed Li 0.5-2x Sr 0.5+x Mx Ta 0.5 Ti 0.5 O3 (Y. Inaguma, A. Seo, T. Katsumata, Solid State Ionics 2004, 174, 19-26), where M represents La and other doping elements, the purpose of which is to partially replace Sr at the A site by La doping, increase the number of vacancies at the A site, and thus improve the lithium ion conductivity of the material. Theoretically, the Cr, Fe, Co, and Ti elements in these structures may be reduced to a low valence state during the lithium insertion reaction, thereby changing the electronic conductivity of the material, but the article does not mention the problem of reduction in contact with the lithium negative electrode, nor does it explore the effect of the content of variable valence elements on the structural stability.

[0007] Currently, there is no reported single-phase mixed ion-electronic conductive interface modification layer based on Sr-based perovskite structure. By introducing variable valence transition metal elements and performing lithium insertion reaction to improve the electronic conductivity of the material, a mixed ion-electronic conductive monomer is obtained. This chemical formula and implementation method are innovative and are expected to be applied to the electrode / electrolyte interface layer of lithium batteries, thereby improving the rate performance and cycle stability of the battery. Summary of the invention

[0008] In order to solve the problems in the prior art, the present invention provides a new type of mixed ion-electron conductor material (mixed conductor) based on perovskite structure, a preparation method and its application in the negative electrode / electrolyte interface of lithium battery. A mixed ion-electron conductor with a perovskite structure, characterized in that the general formula is Li α Sr β X x Ta 1-y-z Y y Z z O3, that is, in the perovskite solid electrolyte Li 0.12 Sr 0.44 The doping X, Y, and Z elements are constructed on the basis of the structure of TaO3 (LSTO), wherein X is selected from one or more of the elements such as Mg, Ca, Ba, and La, Y is a constant valence element, such as selected from Zr, Sn, Al, Ga, and In, and Z is a variable valence element, selected from one or more of the elements Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Ge, Hf, Ta, and W, and the corresponding valence state of Z in the mixed ion-electron conductor at this time is its own high valence state, such as Ti 4+; The ideal perovskite structure is ABO3 type, in which Li, Sr and X occupy the A position of the perovskite structure, and Ta, the fixed valence element Y and the variable valence element Z occupy the B position. In order to maintain the perovskite structure, 0.12≤α≤0.56, 0.3≤β≤0.44, 0.56≤α+β+x≤1 (including x=0, i.e. no X doping) are satisfied. In order to obtain enough free electrons by reducing the variable valence element Z through the insertion of metallic lithium and obtain electronic conductivity properties, 0.11≤z≤0.23 is satisfied. In order to ensure high ionic conductivity of perovskite materials and improve their stability, 0.11≤y+z≤0.50 must be satisfied for comprehensive consideration. When doping different X, Y, and Z elements, the above ratio range can be met.

[0009] Further, the present invention provides a method for preparing a mixed ion-electron conductor with a perovskite structure, characterized in that, according to the structural formula composition of the mixed ion-electron conductor with a perovskite structure, a high-temperature solid-phase method is used to synthesize the corresponding mixed ion-electron conductor in which Z is in a high-valence state, that is, a structure without lithium embedding. The basic process includes the following: using Li2CO3, SrCO3, Ta2O5, binary oxides corresponding to elements X and Y, and binary metal oxides corresponding to the highest valence state of element Z as raw materials, weighing the corresponding synthetic drugs according to the stoichiometric ratio (wherein the lithium salt needs to be in excess of 10%-40%), then grinding them into powder and putting them into a ball mill for ball milling for several hours, pre-sintering the ball-milled powder, and the sintering temperature is 200°C. The sintering time varies with the doping elements and their contents, and is generally within the range of 1000°C-1200°C, with a sintering time of 4-6 hours, after which it is ground into powder again for tableting, and then re-sintered at high temperature, and the high-temperature sintering process is regarded as a phase formation process, and then it is ground into powder again for tableting, and then sintered at high temperature again, and the high-temperature sintering process is regarded as a tableting process; the two high-temperature sintering temperatures are between 1200°C-1400°C, and the sintering time is 8-12 hours. After the ceramic pieces are sintered three times, the mother powder (the powder on the surface) is removed, and then polished with sandpaper, in order to obtain a ceramic piece with a smooth surface and uniform overall thickness, and a mixed ion-electron conductor without lithium embedding can be obtained. The preparation process of this method is relatively simple, the reaction conditions are easy to control, and it is easy to realize industrial production.

[0010] The application of the mixed ion-electron conductor obtained by the present invention is to obtain a lithium-intercalated Li α’ Sr β X x Ta 1-y-z Y y Z zO3, α' is greater than α, and the maximum difference between α' and α corresponds to the total valence reduction of the total amount of Z element from the corresponding high valence state to the corresponding low valence state (the valence change of Z element may be partial, partial or complete); Li embedded in lithium α+m Sr β X x Ta 1-y-z Y y Z z The application of O3 in the negative electrode / electrolyte interface of lithium batteries improves the interface stability;

[0011] The above-mentioned lithium insertion method of the present invention: lithium insertion is carried out in situ or non-in situ by chemical or electrochemical lithium insertion. The specific lithium insertion methods are as follows: (1) The most common method is to react with lithium metal by pre-inserting lithium through heating reaction, that is, placing the mixed ion-electron conductor perovskite ceramic sheet on an electric heating stirrer. The temperature setting of the electric heating stirrer varies with the doping elements, generally 80°C-100°C, and applying appropriate pressure to closely contact the lithium sheet. Lithium will react with the perovskite material. After 5-8 hours, the color of the perovskite ceramic sheet will completely change from white to black, that is, the lithium insertion reaction has occurred; (2) The metal Li is made into powder by mechanical grinding or ball milling and then mixed with the mixed ion-electron conductor perovskite. The mineral materials (powders) are mixed in a certain molar ratio (excessive amount is acceptable), and then a binder (PVDF polyvinylidene fluoride, etc.) and a solvent (NMP, etc.) are added to the mixture. A ball mill is used to stir the mixture to ensure that the lithium powder and the perovskite material are evenly distributed in the slurry. The prepared electrode slurry is evenly coated on the current collector by a coating machine, and then dried. The electrolyte is 1.0M LiPF6 dissolved in EC:DMC:DEC (1:1:1). The electrode sheet is immersed in the electrolyte at room temperature for lithium insertion. This method can adjust the content of embedded lithium by controlling the immersion time and subsequent impedance testing. (3) Pre-lithiation treatment of the mixed ion-electron conductor perovskite ceramic sheet with an organic lithium salt solution, such as immersing the ceramic sheet in a lithium salt solution such as Li-Naph, Li-Bp / THF, and the immersion time is about 5-10 hours to completely insert lithium. This method has uniform contact, and the degree of lithiation can be controlled by the reaction time and the lithium source content. The lithiation process is relatively simple. (4) In-situ lithium insertion through electrochemical cycling, i.e., using the external short circuit method (ESC), that is, the material is connected to the lithium metal negative electrode, and an external resistor or coulomb counter is set to control the current. The current size is controlled by adjusting the resistance value, and constant current charge and discharge tests are performed at room temperature. By observing that the overpotential and interface impedance of the battery are reduced, that is, the electronic conductivity of the material is increased, and a lithium insertion reaction has occurred. (5) The mixed ion-electron conductor perovskite structure material that needs to be pre-lithiated is used as the negative electrode, and lithium metal is used as the positive electrode to assemble into a half-battery. Lithium ions are inserted from lithium metal into the perovskite material through discharge, and the degree of lithium insertion is adjusted by controlling the discharge cut-off voltage.

[0012] Design ideas of the present invention:

[0013] The theoretical design idea of ​​perovskite-based mixed conductor materials is based on Li 0.12 Sr 0.44 The TaO3 structure is doped with elements at positions A and B. The structural formula after doping is Li α Sr β X x Ta 1-y-z Y y Zz O3, of which Li + , Sr 2+ , X g+ Occupies the A position together with O 2- Coordinated, located in the cavity formed by the octahedron. 5+ , Y h+ , Z k+ Occupies position B, with O 2- To ensure the ABO3 structure of perovskite, the tolerance factor t must be within the stable range of 0.75-1. The expression of tolerance factor t is as follows:

[0014]

[0015] Where R A is the average radius of the A-site ion R B is the average radius of the B-site ions R O is the average radius of O ions The closer the tolerance factor t is to 1, the more stable the perovskite structure is, so the principle of making the A-site ion radius as large as possible and the B-site ion radius as small as possible should be followed.

[0016] To ensure the thermodynamic stability of the designed perovskite material, its Gibbs free energy can be calculated by DFT and compared with the sum of the lowest Gibbs free energies of the existing material mixtures in the phase diagram. If the designed material has a lower energy, the material is thermodynamically stable; if the energy of the decomposed mixture is lower, the material tends to decompose. In this way, it is also possible to predict whether the material is easy to synthesize. The compound designed by the present invention does not exist in the existing database, but the stable decomposition product can be found in the existing database, and the mixture ratio with the lowest energy can be found.

[0017] Through DFT calculation of the Gibbs free energy of the material and the energy of its decomposition products, the structure with different content ratios is adjusted to obtain different decomposition energies, thereby screening out more stable perovskite materials.

[0018] The present invention aims to design a new type of material with mixed ion-electron conductive properties based on a perovskite structure. The material is not only required to be thermodynamically stable and easy to synthesize, but also to have high ionic conductivity and electronic conductivity. The ionic conductivity of perovskite fast ion conductors is affected by the lithium concentration and the vacancy concentration. It satisfies the following relationship:

[0019]

[0020] Where n is the Li concentration, that is, the proportion of Li in the A site, n′ is the vacancy concentration, and n cThe void ratio of the body-centered cubic is 0.3117, and μ is 2 in the three-dimensional structure model. α Sr β X x Ta 1-y-z Y y Z z O3 structure, substituting the coefficients of each element in the doping structure into equation 3 yields:

[0021]

[0022] By fixing Li α Sr β X x Ta 1-y-z Y y Z z The content of Sr and X in the O3 structure, with the lithium content α as the independent variable, can be used to calculate the effect of changes in lithium content on the structural ionic conductivity. By adjusting the values ​​of α, β, and x, the aim is to design a perovskite-type fast ion conductor with the most stable structure and the highest ionic conductivity.

[0023] The general formula is Li α Sr β X x Ta 1-y-z Y y Z z The material structure of O3 must satisfy 0.3≤β≤0.44 to ensure the stability of the structure. Since the ionic conductivity of the structure increases first and then decreases with the increase of α, 0.12≤α≤0.55 must be satisfied to ensure a higher ionic conductivity. For the doping of X element at the A position, 0.56≤α+β+x≤1 must be satisfied as a whole. X is selected from Mg, Ca, Ba, La and other elements. If the valence of X is g, α+2β+x×g=1 when not embedded in lithium. To ensure that the metal lithium can be inserted and reduced, In order to obtain enough free electrons by adding valence element Z to obtain electronic conductivity, and considering the number of Li vacancies and limiting the content of Z so as not to affect the structural stability, 0.11≤z≤0.23 and 0.11≤y+z≤0.50 must be satisfied, wherein Y is a constant valence element, such as Zr, Sn, Al, Ga, In and other elements, and Z includes at least one element selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Ge, Hf, Ta, and W. If the valence of Y is h and the valence of Z is k, then α+2β+xg+(h-5)y+(k-5)z=1.

[0024] Through the above various lithium insertion methods, Li α Sr β X x Ta 1-y-z Y y Zz The high-valent Z element in the O3 material structure is reduced to a low-valent state, thereby improving the electronic conductivity of the material and making the material have mixed ion-electron conductive properties. The present invention can be used as a component of a composite material and applied to an electrode layer or an electrolyte layer, wherein the electrode layer or the electrolyte layer contains any of the above-mentioned solid electrolyte materials of the present invention, or contains the above-mentioned composite material with the solid electrolyte material of the present invention as a component. The mixed conductor material designed by the present invention can be applied to energy storage devices such as lithium ion batteries, metal lithium batteries, and all-solid-state lithium batteries.

[0025] The characteristic of this material lies in the introduction of the variable valence element Z. In the experimentally synthesized material, the variable valence element Z is generally the highest oxidation state of the metal. The structure is unstable in the low valence state, but Z can be partially reduced to a low valence state by pre-embedding lithium by heating, in-situ embedding lithium by electrochemical cycling under low potential, etc., thereby improving the electronic conductivity of the material, making the material have mixed ion-electron conductivity and then directly used in lithium batteries.

[0026] The perovskite-based material obtained by modifying and doping a controllable amount of variable-valence elements has mixed ion-electron conductivity and can be used as an interface modification layer between metal lithium and perovskite solid electrolytes, and applied to metal lithium negative electrode protection layers and other electrode material surface coatings, thereby improving interface stability and inhibiting lithium dendrites. This has not been reported in patents and literature related to perovskite electrolytes.

[0027] The material of the present invention has the following advantages:

[0028] 1) The material of the present invention has good chemical stability and mechanical stability;

[0029] 2) The structure of the present invention is based on a fast ion conductor perovskite-type solid electrolyte, matches the perovskite-type solid electrolyte, maintains high ionic conductivity, and eliminates additional interface resistance;

[0030] 3) The present invention introduces variable valence doping elements to obtain doping energy levels, so that the Fermi level after doping is close to the bottom of the conduction band or the top of the valence band, and the electronic conductivity is greatly improved;

[0031] 4) The present invention has mixed ion-electron conductivity properties, and the mixed conductive interface helps to alleviate the overpotential at the interface, uniform ion flux, and achieve uniform deposition of lithium, thereby effectively inhibiting dendrite growth.

[0032] 5) The lithium battery containing the present invention has high ionic conductivity and electronic conductivity, low total resistance, helps to accelerate the charge transfer process, and is suitable for high-rate charging and discharging; and has uniform current distribution, reduces local overcharging, reduces interface reactions, increases interface stability, and thus improves safety;

[0033] 6) The lithium battery of the present invention has a wide operating temperature range and is suitable for a variety of environments. It has good thermal stability and does not affect the cycle life; it still has a high conductivity at low temperatures and can improve the charge and discharge performance at low temperatures;

[0034] 7) The lithium battery of the present invention has a simple manufacturing process, is easy to package, and has a low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of the crystal structure of a doped perovskite-type mixed conductor

[0036] Figure 2 Electronic state density diagram of Ti-doped LSTZO without lithium insertion

[0037] Figure 3 Electronic state density diagram of Ti-doped LSTZO after lithium insertion

[0038] Figure 4 Schematic diagram of LSTTZO-Li interface structure

[0039] Figure 5 LSTTZO-Li interface work function diagram

[0040] Figure 6 Slab model after LSTTZO embedding Li

[0041] Figure 7 Work function diagram of LSTTZO before and after Li embedding (Li9 represents the structure without lithium embedding after cell expansion; Li10 represents the structure after 1 lithium embedding; Li10 represents the structure after 2 lithium embedding; Li12 represents the structure after 3 lithium embedding)

[0042] Figure 8 XPS spectrum of Ta4f orbital when not embedded with lithium

[0043] Fig. 9 XPS spectrum of Ta4f orbital after lithium insertion

[0044] Fig.10 XPS spectrum of Ti2p orbital when not embedded with lithium

[0045] Fig.11 XPS spectrum of Ti2p orbital after lithium insertion

[0046] Fig.12 Impedance diagram of Ti-doped LSTZO in the temperature range of 10℃-30℃ when no lithium is inserted

[0047] Fig.13 Arrhenius plots of ionic conductivity in bulk and at grain boundaries as a function of temperature when Ti-doped LSTZO is not lithium-intercalated

[0048] Fig.14 Constant voltage polarization curves of Ti-doped LSTZO without lithium insertion

[0049] Fig.15 Voltage-current fitting curve of electronic conductivity of LSTTZO after lithium insertion

[0050] Fig.16 Impedance diagram of LSTTZO after lithium insertion at 25°C

[0051] Fig.17 Cycling diagram of Ti-doped interface modified lithium-lithium symmetric battery; the cycling current density is 0.2 mA / cm 2

[0052] Fig.18 Electronic state density diagram of LSLTTZO after lithium insertion

[0053] Fig.19 Interface modification layer lithium-LiNi 0.8 Co 0.1 Mn 0.1 Charge and discharge voltage curve of O2 (NCM-811) asymmetric battery at 0.2C rate

[0054] Fig. 20 LSLTTZO interface modification layer Li-LiNi 0.8 Co 0.1 Mn 0.1 Coulombic efficiency curve of O2 (NCM-811) asymmetric battery at 0.2C rate

[0055] Fig.21 LSTZNO interface modification layer Li-LiNi 0.8 Co 0.1 Mn 0.1 Coulombic efficiency curve of O2 (NCM-811) asymmetric battery at 0.2C rate

[0056] Fig. 22 LSMTSCO interface modification layer lithium-LiNi 0.8 Co 0.1 Mn 0.1 Coulombic efficiency curve of O2 (NCM-811) asymmetric battery at 0.2C rate

[0057] Fig.23 LSBTANO interface modification layer Li-LiNi 0.8 Co 0.1 Mn 0.1 Coulombic efficiency curve of O2 (NCM-811) asymmetric battery at 0.2C rate DETAILED DESCRIPTION

[0058] The present invention is further described below in conjunction with specific embodiments, which are only used to illustrate the present invention and are not limited to the following embodiments. Any modification or equivalent replacement of the technical solution of the present invention without departing from the scope of the technical solution of the present invention shall be included in the protection scope of the present invention.

[0059] Example 1

[0060] ABO3 perovskite structured mixed ion-electron conductor material refers to a material with Figure 1 The stoichiometric ratio of the structure and the non-stoichiometric ratio of the doped perovskite structure. Among them, Li, Sr and the doping element X occupy the A position; Ta and the doping elements Y and Z occupy the B position. Taking the A position with only Li and Sr elements, no X element, and the B position doped with the constant valence element Zr and the variable valence element Ti as an example, adjusting the content of the doping elements can affect the thermal stability and ionic conductivity of the structure. Taking both into consideration, Li 0.34 Sr 0.44 Ta 0.78 Zr 0.11 Ti 0.11 O3. Through DFT theoretical calculation, it is known that Ti doped perovskite structure will react with metal Li to generate lithium-embedded Li 0.45 Sr 0.44 Ta 0.78 Zr 0.11 Ti 0.11 O3, at this time, Ti will change from the original +4 valence to +3 valence. Theoretical calculations show that the room temperature lithium ion conductivity of the product will be lower than that of the previous structure without lithium insertion, but it can still maintain 10 -4 S / cm, which is the same order of magnitude as the ionic conductivity of common fast ion conductors. The size of the electron energy gap determines the electronic conductivity. The electronic state density of the doped material before and after lithium insertion is as follows: Figure 2 , 3 As shown. Figure 2 It can be seen that when lithium is not inserted, the Fermi level is at the top of the valence band, and the band gap between the top of the valence band and the bottom of the conduction band is 2.29 eV. The band gap is wide and the electronic conductivity is low. On this basis, the lithium insertion reaction is carried out, and the electronic state density after lithium insertion is as follows: Figure 3 As shown, the doping energy level enters the bottom of the conduction band, the band gap at the Fermi level is 0, and the material changes from an insulator to an electronic conductor.

[0061] Build Li 0.34 Sr 0.44 Ta 0.78 Zr 0.11 Ti 0.11 O3 perovskite crystal structure model, the chemical formula after cell expansion is Li9Sr 12 Ta 21Zr3Ti3O 81 This structure is combined with the Li slab model to form the LSTZTO-Li structure to simulate the modified layer at the interface between the negative electrode and the electrolyte, such as Figure 4 As shown in the figure, after DFT structural optimization of the structure, it can be seen from the figure that lithium ions naturally move to Li9Sr 12 Ta 21 Zr3Ti3O 81 The structure is diffuse, indicating that the adsorption performance is good and the lithium insertion reaction can be realized experimentally. The work function of the structure after lithium insertion and the lithium metal surface is calculated, and the results are as follows Figure 5 As shown in the figure, it can be seen that the Fermi level of the perovskite mixed conductor structure after lithium insertion is about 2.4eV lower than that of metallic lithium, indicating that electrons in the interface layer can be easily injected, the electronic conductivity is improved, the electric field is uniform, and there is no overpotential. In addition, the electrostatic potential is lower at the position where Ti is present, indicating that electrons tend to be localized near Ti, and Ti is reduced to a low-valence state, thereby protecting the internal electrolyte and preventing electrons from being injected.

[0062] Build Li 0.34 Sr 0.44 Ta 0.78 Zr 0.11 Ti 0.11 O3 perovskite crystal structure model and constructed along the c-axis direction The vacuum layer is embedded on the basis of this structure, and the following are embedded in turn: Figure 6 The work functions of the structure without Li and after 1Li, 2Li, and 3Li are calculated by DFT. The vacuum energy level takes the average potential at half the height of the vacuum layer, from Figure 7 It can be seen that the vacuum energy level of Li-embedded and non-Li-embedded is not much different, and the value is about 3.76eV. As the number of Li-embedded increases, the Fermi level of the structure rises slightly, and the work function value gradually decreases. Because the vacuum energy level is quite different from the Fermi level of the structure, when this structure is used at the negative electrode / electrolyte interface, it will always maintain the Li-embedded structure, that is, Li 0.45 Sr 0.44 Ta 0.78 Zr 0.11 Ti 0.11 O3. It means that the discharge state is maintained during the charge and discharge process, and a high voltage of more than 3.7V is required to remove the surface Li. Therefore, the mixed conductor is difficult to remove lithium and will not reduce the electrolyte, and the structure is relatively stable. Therefore, it is suitable for the negative electrode / electrolyte interface.

[0063] Example 2 (Li 0.34+δ Sr 0.44 Ta 0.78 Zr 0.11 Ti 0.11O3)

[0064] Synthesis of Li by high temperature solid phase method 0.34 Sr 0.44 Ta 0.78 Zr 0.11 Ti 0.11 O3, Li2CO3, SrCO3, ZrO2, Ta2O5, TiO2 are used as raw materials, and the corresponding drug mass is weighed according to the stoichiometric ratio. After the drug is ground into powder, it is ball-milled for 5 hours with ZrO2 balls, and then the slurry is dried and placed in an alumina crucible for 1100°C, 5 hours of pre-sintering treatment, and then the sample is re-grinded and pressed into tablets, and then covered with mother powder, and sintered at 1350°C for 6 hours to obtain an ABO3 type perovskite structure, and then the sample is re-grinded and pressed into tablets, and then covered with mother powder and calcined at 1300°C for 10 hours. The purpose is to make the LSTTZO after phase formation more dense. Finally, it is polished to obtain a dense ceramic sheet lithium ion conductor.

[0065] XPS was used to test the valence states of Ta and Ti in LSTZTO before and after lithium insertion. Figure 8 and Fig. 9 It can be seen from the XPS spectrum that the valence state of Ta does not change significantly before and after lithium insertion. There are two Ta atoms at the binding energy positions of 26.0 eV and 27.8 eV. 5+ The characteristic peaks of Ta4f before and after lithium insertion are all due to Ta 5+ 4f 7 / 2 and 4f 5 / 2 The two peaks indicate that Ta is not reduced. Fig.10 This is the XPS spectrum of Ti2p before lithium insertion, with two Ti2p atoms at binding energies of 458.9 eV and 464.8 eV. 4+ However, after lithium insertion, additional suboxidation peaks appeared in the XPS spectrum of Ti2p, such as Fig.11 As shown, it indicates that part of Ti is reduced from tetravalent to low-valent state, which is consistent with theoretical calculation.

[0066] The ionic conductivity of perovskite ceramic materials was measured by EIS impedance method. The Zviewr software was used to build an equivalent circuit and the grain boundary impedance at a temperature of 10°C-30°C was obtained by fitting the EIS. Fig.12 The bulk conductivity R of the material at 30°C can be obtained b is 152.5Ω, the grain boundary resistance R gb is 138.4Ω, so the total ionic conductivity of the material structure at 30°C can be calculated to be 4.24×10 -4 S / cm. The Arrhenius curves of the ionic conductivity of the bulk phase and the grain boundary as a function of temperature are shown in Fig.13 As shown, it can be seen that the activation energy of ion migration in the perovskite structure phase has almost no effect on the change of temperature, but the activation energy of ion migration at the grain boundary of the perovskite structure under the temperature condition below -40°C obviously requires a higher activation energy of 0.44eV to realize the ion migration of lithium ions at the grain boundary. When it is higher than -40°C, the activation energy of lithium ion migration at the grain boundary is reduced to 0.36eV.

[0067] The electronic conductivity of the material was tested using the double blocking electrode method. The ceramic sheet without lithium embedding was subjected to constant voltage polarization at 25°C. The ion blocking electrode used a sputtered gold electrode. The polarization voltage was 0.1V. After the voltage was applied, the current dropped rapidly from a large value. At this time, lithium ions moved from the positive electrode to the negative electrode to form an ion current, and electrons moved from the negative electrode to the positive electrode to form an electronic current. The current size was the sum of the ion current and the electronic current. As time went on, the concentration of lithium ions was high at the negative electrode and low at the positive electrode, forming a concentration potential, which ultimately hindered the movement of lithium ions, and only the directional movement of electrons remained. The results are as follows: Fig.14 As shown, the un-lithium-intercalated Li 0.34 Sr 0.44 Ta 0.78 Zr 0.11 Ti 0.11 The electronic conductivity of O3 is 1.48×10 -8 S / cm. This indicates that the structure without lithium insertion has no electronic conductivity. The perovskite ceramic sheet is placed on an electric heating stirrer, the temperature of the electric heating stirrer is set to 100°C, and appropriate pressure is applied to keep it in close contact with the lithium sheet. Lithium will react with the perovskite material. After 6 hours, the color of the perovskite ceramic sheet will change from white to black, indicating that a lithium insertion reaction has occurred. The content of lithium insertion can be adjusted by controlling the heating time and observing the impedance change. Lithium can be inserted to generate a mixed conductor Li 0.34+δ Sr 0.44 Ta 0.78 Zr 0.11 Ti 0.11 O3 (0<δ≤0.11). At this time, part of Ti will be reduced from positive tetravalent to positive trivalent, and it will not cause Ti to 4+ Reduction to metallic Ti. The Hebb–Wagner method was used to assemble the Li-LSTTZO-Au battery. The ceramic sheet after lithium insertion was subjected to constant voltage polarization test at room temperature. The electronic current and ion current in the steady-state current were quantitatively analyzed to obtain the fitting curve of voltage and current, as shown in Figure 2. Fig.15 As shown in the figure, the electronic conductivity of the ceramic sheet after lithium insertion is calculated by Ohm's law to be 9.3×10 -4S / cm. The electronic conductivity is greatly improved compared with that before lithium insertion. The ionic conductivity after lithium insertion is obtained by EIS and DC constant voltage polarization. The electrochemical impedance spectrum of the mixed conductor after lithium insertion is tested, such as Fig.16 As shown, a polarization voltage of 0.1 V is selected, and the Li after lithium insertion is obtained by combining the above electronic conductivity with the series-parallel formula. 0.34+δ Sr 0.44 Ta 0.78 Zr 0.11 Ti 0.11 The ionic conductivity of O3 is 2.85×10 -4 S / cm.

[0068] The Ti-doped perovskite mixed conductor was used as the interface modification layer, and the perovskite ceramic sheet was applied to a lithium-lithium symmetric battery, in which the positive and negative electrodes were both lithium, the electrolyte was commercial LiPF6, and the electrolyte was dissolved in three organic mixtures with equal volume ratios, i.e., EC:DMC:DEC=1:1:1Vol%, the total molar concentration of the electrolyte was 1.0M, and the cycle current density was 0.2mA / cm 2 .like Fig.17 As shown, it can be seen that the battery can still maintain normal working condition after 800 hours of cycle.

[0069] Example 3 (Li 0.20 Sr 0.30 La 0.14 Ta 0.78 Zr 0.11 Ti 0.11 O3)

[0070] In Li 0.12 Sr 0.44 Based on the TaO3 structure, La is selectively doped at the A site, and Zr and Ti are simultaneously doped at the B site to obtain Li 0.20 Sr 0.30 La 0.14 Ta 0.78 Zr 0.11 Ti 0.11 O3. The chemical formula after lithium insertion is Li 0.31 Sr 0.30 La 0.14 Ta 0.78 Zr 0.11 Ti 0.1 1O3, at this time, Ti is reduced from positive tetravalent to positive trivalent, which is the same as Example 2. Fig.18 It can be seen that the structural band gap after Li insertion is 0, indicating that it has been transformed into an electronic conductor.

[0071] The synthesis method is the same as that in Example 2, that is, a high-temperature solid-phase method is used to synthesize a structure without lithium insertion. The lithium insertion method uses an organic lithium salt solution to pre-lithiate the perovskite ceramic sheet. The experimental process is roughly as follows: first, prepare the organic lithium salt Li-Bp and the organic solvent THF to make a 0.1M concentration lithium salt solution, and immerse the cleaned and dried perovskite ceramic sheet in the Li-Bp / THF lithium salt solution, maintain a constant temperature of 50°C, and immerse for about 5 hours. The degree of lithiation can also be controlled by setting different immersion times and temperatures, as well as subsequent electrochemical impedance tests. After immersion, the ceramic sheet is taken out and cleaned and dried. The electronic conductivity of the structure after lithium insertion is 8.8×10 -4 S / cm, and the ionic conductivity is 4.86×10 -4 S / cm, indicating that lithium insertion is successful, part of Ti is reduced from positive tetravalent to low-valent state, and is not reduced to metal. Compared with the structure without La doping in Example 2, the ionic conductivity of the structure is improved after the additional addition of La, because doping increases the disorder of the structure and thus increases the entropy value, promotes the distortion of the lattice, and reduces the activation energy required for ion migration. However, since La replaces Sr in the A position, the Sr element mainly plays the role of supporting the cubic structure, so the thermal stability of the structure may be reduced.

[0072] The mixed conductor ceramic sheet is applied to Li-LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM-811) asymmetric battery, where the electrolyte is Li 0.35 La 0.55 TiO3. The charge and discharge voltage curves of the first and fiftieth cycles of the battery at a rate of 0.2C are shown in Fig.19 As shown, the Coulomb efficiency curve is as follows Fig. 20 As shown in the figure, we can see that after 50 cycles of the battery, the capacity can be maintained at 168mAh / g, the capacity retention rate is about 94%, the capacity loss is small, the battery performance is better and can still maintain normal working condition.

[0073] Example 4 (Li 0.23 Sr 0.44 Ta 0.78 Zr 0.11 Nb 0.11 O3)

[0074] In Li 0.12 Sr 0.44 Based on the TaO3 structure, Li is obtained by doping trace Zr and Nb elements at the B position. 0.23 Sr 0.44 Ta 0.7 8Zr 0.11 Nb0.11 O3, wherein Nb is pentavalent. The synthesis method is the same as that in Example 2, that is, a high-temperature solid-phase method is used to synthesize a structure without lithium insertion, and then the material is pre-lithiated. The general process is to add the perovskite material to NMP solvent, add carbon black conductive agent and PVDF binder, and then evenly coat it on copper foil to form a negative electrode layer. Lithium metal is used as the positive electrode. The electrolyte is 1.0M LiPF6 dissolved in EC:DMC:DEC (1:1:1). After assembling into a half-cell, lithium ions are inserted from lithium metal into the perovskite material at a discharge rate of 0.1C. The degree of lithium insertion can be adjusted by setting different discharge cut-off voltages. This embodiment adopts a step-by-step discharge method, that is, the initial discharge is performed with 1.0V as the termination voltage, and then the termination voltage is gradually reduced to 0.1V. After each discharge, the degree of lithium insertion in each stage is determined by detecting the changes in current, voltage, and discharge capacity. After the discharge, the electronic conductivity of the structure after lithium insertion is 4.7×10 -4 S / cm, and the ionic conductivity is 1.59×10 -4 S / cm. This indicates that lithium insertion is successful, and part of Nb is reduced from pentavalent to low-valent state, and is not reduced to metal. The mixed conductor ceramic sheet is applied to Li-LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM-811) asymmetric battery, where the electrolyte is Li 0.35 La 0.55 TiO3, parameters are the same as in Example 3, Coulomb efficiency curve is as follows Fig.21 As shown in the figure, we can see that after 50 cycles of the battery, the capacity can be maintained at 141mAh / g, and the capacity retention rate is about 90%.

[0075] Example 5 (Li 0.34 Sr 0.33 Mg 0.11 Ta 0.78 Sn 0.11 Co 0.11 O3)

[0076] In Li 0.12 Sr 0.44 Based on the TaO3 structure, Li is obtained by doping Mg at the A site and trace Sn and Co at the B site. 0.34 Sr 0.33 Mg 0.11 Ta 0.78 Sn 0.11 Co 0.11O3. Co is a variable valence element. The synthesis method is the same as that in Example 2, that is, a high-temperature solid phase method is used to synthesize a structure without lithium insertion. At this time, Co in the structure is positive tetravalent. Then, the metal Li is made into powder by a ball mill and mixed with the perovskite material. Then, PVDF binder and solvent NMP are added to the mixture. The mixture is stirred by a ball mill to ensure that the lithium powder and the perovskite material are evenly distributed in the slurry. The prepared electrode slurry is evenly coated on the current collector by a coating machine, and then dried. The electrolyte is 1.0M LiPF6 dissolved in EC:DMC:DEC (1:1:1). The electrode sheet is immersed in the electrolyte for lithium insertion. The method can adjust the content of embedded lithium by controlling the immersion time and subsequent impedance testing. After immersion for 6 hours, the electronic conductivity and ionic conductivity calculation test of the structure after lithium insertion are performed. The method is the same as that in Example 2. The electronic conductivity of the structure after lithium insertion is 7.5×10 -4 S / cm, and the ionic conductivity is 3.32×10 -4 S / cm. This indicates that lithium insertion is successful, and part of Co is reduced from positive tetravalent to low-valent state, and is not reduced to metal. The mixed conductor ceramic sheet is also applied to Li-LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM-811) asymmetric battery, the electrolyte is the same as Li 0.35 La 0.55 TiO3, parameters are the same as in Example 3, Coulomb efficiency curve is as follows Fig. 22 As shown, after 50 cycles of the battery, the capacity can be maintained at 160 mAh / g, and the capacity retention rate is about 93%.

[0077] Example 6 (Li 0.45 Sr 0.33 Ba 0.11 Ta 0.78 Al 0.11 Ni 0.11 O3)

[0078] In Li 0.12 Sr 0.44 Based on the TaO3 structure, Li is obtained by doping Ba at the A site and Al and Ni at the B site. 0.45 Sr 0.33 Ba 0.11 Ta 0.78 Al 0.11 Ni 0.11O3. Ni is a variable-valence element, and the preparation method is the same as that in Example 2, that is, a high-temperature solid-phase method is used to synthesize a structure without lithium insertion. At this time, Ni in the structure is tetravalent, and then Ni is reduced to trivalent by in-situ lithium insertion through electrochemical cycles. The preparation process of lithium insertion is the same as that in Example 4, except that the material is connected to the lithium metal negative electrode by an external short-circuit method (ESC), and a coulomb counter is set to control the current. Constant current charging and discharging is performed at room temperature. By observing that the overpotential and impedance changes of the battery are reduced, that is, the electronic conductivity of the material is increased, and a lithium insertion reaction has occurred, the content of lithium insertion can be adjusted by setting different external resistance values ​​and monitoring voltage and impedance changes. Perform multiple electrochemical cycles until the termination voltage of 0.1V is reached, and then stop discharging. At this time, the electronic conductivity and ionic conductivity of the structure after lithium insertion are calculated and tested in the same way as in Example 2, and the electronic conductivity of the structure after lithium insertion is 7.1×10 -4 S / cm, and the ionic conductivity is 3.52×10 -4 S / cm. This indicates that lithium insertion is successful, and part of Ni is reduced from positive tetravalent to low-valent state, and is not reduced to metal. The mixed conductor ceramic sheet is also applied to Li-LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM-811) asymmetric battery, the electrolyte is the same as Li 0.35 La 0.55 TiO3, parameters are the same as in Example 3, Coulomb efficiency curve is as follows Fig.23 As shown, after 50 cycles of the battery, the capacity can be maintained at 163 mAh / g, and the capacity retention rate is about 93%.

[0079] The ionic-electronic conductivity of each material after lithium insertion in the above embodiments and the application of Li-LiNi 0.8 Co 0.1 Mn 0.1 The performance statistics of the O2 (NCM-811) asymmetric battery are shown in Table 1. By modifying and doping the elements contained in the LSTO electrolyte, the valence state and the number of combinations are limited to obtain a high-entropy solid electrolyte interface modification layer containing lithium vacancies, thereby effectively improving the battery cycle performance.

[0080] Table 1 Example Effect

[0081]

[0082] The results of the above examples show that the doped perovskite-type mixed conductor has high ionic conductivity and electronic conductivity. The material of the present invention can match the negative electrode and be applied to the electrode / electrolyte interface modification of all-solid-state lithium batteries, which can improve the cycle stability and safety of the battery.

[0083] The invention of this application is not limited to the embodiments described above. Professional and technical personnel in this field can make several possible changes and modifications and implement them in other embodiments without departing from the conceptual principles of this application. Therefore, the scope of protection of this application should be based on the scope defined by the claims of this application.

Claims

1. A mixed ion-electron conductor of a perovskite structure, characterized in that: The general formula is Li α Sr β X x Ta 1-y-z Y y Z z The perovskite structure of O3, wherein X is selected from one or more of Mg, Ca, Ba, and La elements, Y is a constant valence element selected from Zr, Sn, Al, Ga, and In elements, and Z is a variable valence element selected from one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Ge, Hf, Ta, and W elements, and the corresponding valence state of Z in the mixed ion-electron conductor at this time is its own high valence state, 0.12≤α≤0.56, 0.3≤β≤0.44, 0.56≤α+β+x≤1, which includes x=0, that is, no X is doped, wherein the range of the variable valence element Z is 0.11≤z≤0.23, and satisfies 0.11≤y+z≤0.

50.

2. A mixed ion-electron conductor of a perovskite structure according to claim 1, characterized in that: The perovskite structure is of ABO3 type, in which Li, Sr and X occupy the A position of the perovskite structure, and Ta, the fixed valence element Y and the variable valence element Z occupy the B position.

3. A method for preparing a mixed ion-electron conductor with a perovskite structure as claimed in claim 1 or 2, characterized in that: According to the structural formula of the mixed ion-electron conductor, a high-temperature solid-phase method is used to synthesize the corresponding mixed ion-electron conductor in which Z is in a high-valent state, that is, a structure without lithium embedding. The basic process includes the following: Li2CO3, SrCO3, Ta2O5, binary oxides corresponding to elements X and Y, and binary metal oxides corresponding to the highest valence state of element Z are used as raw materials, and the corresponding synthetic drugs are weighed according to the stoichiometric ratio, wherein the lithium salt is in excess of 10%-40%, and then ground into powder and put into a ball mill for several hours of ball milling, and the ball-milled powder is pre-sintered, and the sintering temperature and sintering time vary with the doping elements and their contents. The temperature of the ceramic sheet is generally between 1000°C and 1200°C, the sintering time is 4-6 hours, and then it is ground into powder again for tableting, and then re-sintered at high temperature. The high-temperature sintering process is regarded as a phase forming process, and then it is ground into powder again for tableting, and then sintered at high temperature again. The high-temperature sintering process is regarded as a tableting process; the two high-temperature sintering temperatures are between 1200°C and 1400°C, and the sintering time is 8-12 hours. After the ceramic sheet is sintered three times, the mother powder is removed and polished with sandpaper to obtain a ceramic sheet with a smooth surface and uniform overall thickness, so as to obtain a mixed ion-electron conductor without lithium embedding.

4. Application of a mixed ion-electron conductor with a perovskite structure as claimed in claim 1 or 2, wherein the material obtained by inserting lithium into the mixed ion-electron conductor is applied to the negative electrode of a lithium battery.

5. According to the application of claim 4, the lithium battery is any energy storage device such as a lithium ion battery, a metal lithium battery, an all-solid-state lithium battery, etc., and the application is applied to at least one of a negative electrode layer, an electrode / electrolyte interface layer, and an electrode surface coating material.

6. The use according to claim 4, wherein the mixed ion-electron conductor is Li α’ Sr β X x Ta 1-y-z Y y Z z O3, α' is greater than α, and the maximum difference between α' and α corresponds to the total valence reduction of the total amount of the element Z from the corresponding high valence state to the corresponding low valence state. Here, the valence change of the element Z is partial change, partial no change, or complete change.

7. The use according to any one of claims 4 to 6, characterized in that: Lithium insertion method: Lithium insertion can be performed in situ or non-situ by chemical or electrochemical lithium insertion. Specific lithium insertion methods include the following: (1) Pre-insertion of lithium with lithium metal by heating reaction, that is, placing the mixed ion-electron conductor perovskite ceramic sheet on an electric heating stirrer. The temperature setting of the electric heating stirrer varies with the doping elements, generally 80°C-100°C, and applying appropriate pressure to keep the lithium sheet in close contact. Lithium will react with the perovskite material. After 5-8 hours, the color of the perovskite ceramic sheet will change from white to black, indicating that a lithium insertion reaction has occurred; (2) Mechanically grind the metal Li into powder or ball mill and mix it with the mixed ion-electron conductor perovskite material. The materials (powders) are mixed in a certain molar ratio (excessive amount is acceptable), and then a binder (PVDF polyvinylidene fluoride, etc.) and a solvent (NMP, etc.) are added to the mixture, and a ball mill is used to stir to ensure that the lithium powder and the perovskite material are evenly distributed in the slurry. The prepared electrode slurry is evenly coated on the current collector by a coating machine, and then dried. The electrolyte is 1.0M LiPF6 dissolved in EC:DMC:DEC (1:1:1), and the electrode sheet is immersed in the electrolyte at room temperature for lithium insertion. This method can adjust the content of embedded lithium by controlling the immersion time and subsequent impedance testing. (3) Pre-lithiation treatment of mixed ion-electron conductor perovskite ceramic sheets with organic lithium salt solution, such as immersing the ceramic sheet in lithium salt solutions such as Li-Naph, Li-Bp / THF, and the immersion time is about 5-10 hours to completely insert lithium. This method has uniform contact, and the degree of lithiation can be controlled by reaction time and lithium source content. The lithiation process is relatively simple. (4) In-situ lithium insertion through electrochemical cycling, i.e., using the external short circuit method (ESC), that is, the material is connected to the lithium metal negative electrode, and an external resistor or coulomb counter is set to control the current. The current size is controlled by adjusting the resistance value, and constant current charge and discharge tests are performed at room temperature. By observing that the overpotential and interface impedance of the battery are reduced, that is, the electronic conductivity of the material is increased, and a lithium insertion reaction has occurred. (5) The mixed ion-electron conductor perovskite structure material that needs to be pre-lithiated is used as the negative electrode, and lithium metal is used as the positive electrode to assemble into a half-battery. Lithium ions are inserted from lithium metal into the perovskite material through discharge, and the degree of lithium insertion is adjusted by controlling the discharge cut-off voltage.

8. A lithium battery, characterized in that: A material containing the mixed ion-electron conductor of the perovskite structure according to claim 1 after lithium insertion.